2009
DOI: 10.2478/s11686-009-0005-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal parasites in shelter dogs and cats in the metropolitan area of Barcelona (Spain)

Abstract: Prevalence of intestinal parasites in dogs and cats in Barcelona and surrounding areas was studied by analyzing 505 faecal samples of dogs and 50 of cats using a formol-ether diphasic method for helminths, a modified acid-fast technique for Cryptosporidium and other coccidian oocysts, and the Heindenhein technique for Giardia and Entamoeba trophozoites and cysts. Parasites were found in 26.9% of dogs and 34.0% of cats. Giardia duodenalis, Cryptosporidium sp., coccidian oocysts and Entamoeba sp. were detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 21 publications
6
26
0
3
Order By: Relevance
“…A recent study conducted to determine the prevalence of GI parasites in Barcelona, Spain reported prevalence rates of Entamoeba spp. of 0.4% in the surveyed dogs and cats (Gracenea et al 2009). However, the risk to public health from zoonotic transmission of Entamoeba spp.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study conducted to determine the prevalence of GI parasites in Barcelona, Spain reported prevalence rates of Entamoeba spp. of 0.4% in the surveyed dogs and cats (Gracenea et al 2009). However, the risk to public health from zoonotic transmission of Entamoeba spp.…”
Section: Discussionmentioning
confidence: 97%
“…3 Dog plays important role in the epidemiology of some parasitic infections that affect humans, thereby making the control of those parasites in dogs a public health concern. 4,5 Dogs shed oocysts, eggs or larvae of zoonotic parasites into the environment and humans get infected directly through contact with dog or faeces containing infective stage of the parasites or indirectly through ingestion of contaminated water and/or food. 3 Two important examples of zoonotic parasites of dogs are Ancylostoma caninum and Toxocara canis.…”
Section: Introductionmentioning
confidence: 99%
“…10]. However, there is no any information cases, the animals come in close contact with humans on the literature on the prevalence of gastrointestinal and their dwellings and act as reservoirs and helminth parasites of pet and stray dogs in Bahir dar transmitters of zoonotic diseases [5,6]. Gastrointestown, Therefore, the objectives of this study were to tinal helminths of dogs pose serious impact both on the identify and determine the prevalence of GI helminth host and human beings.…”
Section: Introductionmentioning
confidence: 99%